Medical Affairs in Pharmaceutical Companies and Related Pharmaceutical Regulations in Japan - Maeda, Hideki (Frontiers in Medicine, 2021)
Medical affairs has received a lot of attention in recent years in Japan, but it is also often misunderstood or poorly understood in the healthcare industry in Japan. In the United States, the function of medical affairs has been established for a long time, whereas its history in Japan is relatively short. Many scandals in clinical trials occurred with inappropriate relationship between medical doctors and the sales departments of pharmaceutical companies from 2012. These incidents undermined confidence in clinical trials in Japan and triggered the enforced separation of sales departments from the conduct of post-marketing clinical trials and evidence generation. There have been growing compliance issues identified in marketing and sales practices, and off-label promotion is also becoming an issue in Japan. These issues resulted in the establishment of independent medical affairs departments from sales departments in pharmaceutical companies operating in Japan. Due to the short history of medical affairs in Japan, the roles and responsibilities vary between companies in Japan. Medical affairs departments aim to fulfill unmet medical needs through the generation of scientific evidence and to deliver scientific value to key stakeholders and patients. People working in medical affairs need to engage in scientific exchange activities with key opinion leaders independent of sales departments. Through these activities, medical affairs ensures that patients receive optimal medical care. Medical affairs in Japan is still developing, and its roles, responsibilities, and functions are improving. This article covers the history of medical affairs in Japan and the current status and future perspectives of medical affairs in Japan.